2007
DOI: 10.1002/pssa.200673013
|View full text |Cite
|
Sign up to set email alerts
|

Optical and magneto‐optical properties of ZnMnO and ZnMnFeO single crystals and thin films

Abstract: Single crystals of oxide diluted magnetic semiconductor Zn1–x Mnx O have been grown by chemical vapour transport and thin films of Zn1–x Mnx O, Zn1–x –y Mnx Fey O have been deposited by pulsed laser ablation and rf magnetron sputtering methods. Optical absorption spectra of the obtained crystals and films have features associated with band‐to‐band direct type transitions and d–d crystal‐field transitions due to presence of Mn2+ ions. The observed peculiarities of the Faraday rotation for Zn1–x Mnx O crystals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Previous studies of magneto‐optical Faraday effect in oxide SMS bulk crystals and thin films 22–24 allowed to find paramagnetic behaviour in ternary Zn 1 − x Mn x O and ferromagnetic ordering in Zn 0.88 Mn 0.05 Fe 0.07 O thin films. The present results confirm room temperature ferromagnetism in co‐doped Zn 0.88 Mn 0.05 Fe 0.07 O thin films, but suggest of absence of similar magnetic behaviour for new quaternary Zn 0.93 Mn 0.03 Sn 0.04 O oxides.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies of magneto‐optical Faraday effect in oxide SMS bulk crystals and thin films 22–24 allowed to find paramagnetic behaviour in ternary Zn 1 − x Mn x O and ferromagnetic ordering in Zn 0.88 Mn 0.05 Fe 0.07 O thin films. The present results confirm room temperature ferromagnetism in co‐doped Zn 0.88 Mn 0.05 Fe 0.07 O thin films, but suggest of absence of similar magnetic behaviour for new quaternary Zn 0.93 Mn 0.03 Sn 0.04 O oxides.…”
Section: Resultsmentioning
confidence: 98%
“…Mechanisms of superexchange, double exchange, free‐carrier‐mediated exchange and exchange through bound magnetic polaron have been involved to explain the ferromagnetic ordering above room temperature 15–21. It was shown in our previous studies that Zn 1 − x Mn x O single crystals and thin films demonstrate paramagnetic behaviour 22, 23, whereas for Zn 1 − x − y Mn x Fe y O thin films ferromagnetism was experimentally confirmed 24. In this work, we report on complex study of electrical, structural, optical and magneto‐optical properties of ternary and quaternary SMS oxides in form of thin films and nanocrystals.…”
Section: Introductionmentioning
confidence: 97%
“…Among these methods, RF reactive sputtering technique is less studied. Savchuk et al [19][20][21][22] have demonstrated paramagnetic behaviours of ZnMnO thin films and ferromagnetic ordering in co-doped quaternary ZnMnFeO oxides prepared by RF sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…Коваль (запропоновано методичні рекомендації щодо корекції поведінки дітей з особливими потребами), 0. Прокоф'єва [6] (досліджено показники інтегральних форм соціальної агресивності, рівень самооцінки та самопочуття в соціумі батьків, які виховують дітей з особливими потребами; розроблено корекційну програму оптимізації особистісної сфери таких батьків), Л. Савчук [7] (висвітлено особливості сімей, що негативно впливають на формування особистості дітей), Т.Соловйова [8] (удосконалено зміст, форми та методи соціально-педагогічної роботи з батьками; виокремлено критерії та рівні адаптації батьків до життєвих умов, ускладнених інвалідністю дитини) та інших.…”
unclassified